Walkability analysis for improvement: prioritizing potential walkability projects in a high-vacancy environment - Randall, Scott Christopher (Kansas State University, 2020)
Neighborhood walkability has been associated with several benefits including Improved physical health, improved mental health and improved social capital. However, many cities have poor walking environments and consequently do not enjoy these benefits. While several walkability analysis tools have been developed to understand and identify walkability challenges, none account for urban vacancy. Furthermore, although these existing tools provide a wealth of data but do not directly support community members, designers and planners in comparing and selecting walkability improvement projects. This project focuses on evaluating walkability in a high-vacancy neighborhood in Kansas City, Missouri for the purpose of exploring the quality of the walking environment in a high-vacancy setting and rating areas of the project site to identify areas in greatest need of walkability improvement. The addition of considerations for urban vacancy add an additional dimension of analysis to provide some adjustment for the challenges of a high-vacancy setting. The framework for this case study is based on the Hierarchy of Walking Needs concept, which postulates that the decision to walk is the result of meeting several types of needs, and that certain basic-level needs must be met before higher level needs. This project focuses on the 2nd-, 3rd- and 4th-level needs which are accessibility (walking infrastructure), safety (safety from crime and traffic) and comfort (level of physical ease and sensory comfort afforded by the environment). GIS mapping and Google Earth were used to analyze the built environment of the project site to evaluate analyze walkability for the development of a tool that will help decision-makers and stakeholders by providing a structure to identify, evaluate and compare potential areas for walkability improvement. This tool, called the Walkability Improvement Prioritization Tool, is intended to help establish priority areas for walkability improvement to optimize the use of limited resources in high- and low-vacancy settings.
Keywords: Walkability; Urban vacancy; Walkability audit